Reconnection-Less Electronically Reconfigurable Filter with Adjustable Gain Using Voltage Differencing Current Conveyor - Jerabek, Jan; Sotner, Roman; Polak, Josef; Vrba, Kamil; Dostal, Tomas (Elektronika ir Elektrotechnika, 2016)
This paper presents a novel reconnection-less and electronically reconfigurable analogue filter. It employs two active elements, Voltage-Differencing Current Conveyor (VDCC) and Dual-Output Current Amplifier (DO-CA) with two independently tunable gains. Filter has the single input and single output topology (SISO). The current-mode transfer function of the filter can be tuned electronically from the low-pass (LP) response to the high-pass (HP) response, via the band-stop (BS) response, without reconnection of the input or output terminal. It is designed in order to provide tuning of both the stop-band gain and also pass-band gain of all the transfer functions, because also transfer functions with additional and intended zero in transfer function are available. The theoretical presumptions are confirmed by both simulations and lab measurements with available devices. DOI: http://dx.doi.org/10.5755/j01.eie.22.6.17221